TREM-1 Mediates Inflammatory Injury and Cardiac Remodeling Following Myocardial Infarction. Issue 11 (22nd May 2015) - Boufenzer, Amir; Lemarié, Jérémie; Simon, Tabassome; Derive, Marc; Bouazza, Youcef; Tran, Nguyen; Maskali, Fatiha; Groubatch, Frédérique; Bonnin, Philippe; Bastien, Claire; Bruneval, Patrick; Marie, Pierre-Yves; et al.
<x xml:space="preserve">Abstract</x> Rationale: Optimal outcome after myocardial infarction (MI) depends on a coordinated healing response in which both debris removal and repair of the myocardial extracellular matrix play a major role. However, adverse remodeling and excessive inflammation can promote heart failure, positioning leucocytes as central protagonists and potential therapeutic targets in tissue repair and wound healing after MI. Objective: In this study, we examined the role of triggering receptor expressed on myeloid cells-1(TREM-1) in orchestrating the inflammatory response that follows MI. TREM-1, expressed by neutrophils and mature monocytes, is an amplifier of the innate immune response. Methods and Results: After infarction, TREM-1 expression is upregulated in ischemic myocardium in mice and humans. Trem-1 genetic invalidation or pharmacological inhibition using a synthetic peptide (LR12) dampens myocardial inflammation, limits neutrophils recruitment and monocyte chemoattractant protein-1 production, thus reducing classical monocytes mobilization to the heart. It also improves left ventricular function and survival in mice (n=20–22 per group). During both permanent and transient myocardial ischemia, Trem-1 blockade also ameliorates cardiac function and limits ventricular remodeling as assessed by fluorodeoxyglucose-positron emission tomographic imaging and conductance catheter studies (n=9–18 per group). The soluble form of TREM-1 (sTREM-1), a marker of TREM-1 activation, is detectable in the plasma of patients having an acute MI (n=1015), and its concentration is an independent predictor of death. Conclusions: These data suggest that TREM-1 could constitute a new therapeutic target during acute MI.